Peran Pemerintah Daerah dalam Mengembangkan Objek Wisata di Danau Tiwu Sora, Desa Tiwu Sora, Kecamatan Lepembusu Kelisoke, Kabupaten Ende - Maria Ines T. Ndepi; Ananias R. P. Jacob; Frans W. Muskanan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is entitled “The Role of Local Government in Developing Tourism Objects at Tiwu Sora Lake, Tiwu Sora Village, Lepembusu Kelisoke District, Ende Regency”. This study aims to determine the role of local government in developing tourist attractions at Lake Tiwu Sora. This research discusses the role of government in the implementation of tourist attraction development and there are suggestions to provide input to the local government. This research design uses qualitative research methods and descriptive approaches. The author uses data collection techniques of observation, interviews, documentation in the data collection process besides that there are data analysis techniques using the method of reduction, presentation and conclusion drawing. The results of this study indicate that the role of the local government in developing the Lake Tiwu Sora tourist attraction has not gone well as evidenced by the many facilities at the tourist attraction that are not well cared for, and the road to the Lake Tiwu Sora tourist attraction is damaged. In the process of developing tourist attractions, the local government pays attention to the socio-economics of village communities in tourist attractions by forming tourism awareness groups.